E-Billing System, Sanksi Perpajakan, Kualitas Pelayanan dan Kepatuhan Wajib Pajak Era Pandemi Covid-19 - Sura, Ni Made Dwi Pratiwi; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
The research aims to test empirically the effect of implementing the e-billing system, tax sanctions and service quality on tax compliance in the Covid-19 pandemic era. The study uses the Theory of Planned Behavior and Attribution Theory, with a population of 140,595 registered taxpayers at the East Denpasar Pratama Tax Office with a total sample of 100 respondents obtained by the slovin formula. The sample collection method uses a non-probability sampling method with a purposive sampling technique. The data collection method uses a questionnaire with multiple linear regression data analysis techniques. The results showed that the implementation of the e-billing system, tax sanctions and service quality had a significant positive effect on taxpayer compliance in the Covid-19 pandemic era. Keywords: E-Billing System; Tax Sactions; Quality of Tax Service; Taxpayer Compliance